DOUBLE DUTIES: PAJAK DAN SUMBANGAN KEAGAMAAN DALAM PERSPEKTIF MASYARAKAT HINDU BALI (Studi pada Wajib Pajak Orang Pribadi Umat Hindu Perantauan Asal Bali Di Sektor Tropodo Sidoarjo) - Made Dudy Satyawan; Lintang Venusita (Universitas Trunojoyo Madura, 2014)
This study aims to explore the practice of giving Punia Hindu Balinese community in Sidoarjo Tropodo. Phenomenological qualitative research approach that connects between the attitudes and behaviours of Hindus who pay taxes to fund events Punia and issuance of Government Regulation No. 60 in 2010 and other relevant tax laws. Dana Punia is a form of religious endowments to Hindus which is compulsory that can be deducted from income payments through Badan Dharma Dana Nasional. Techniques of data analysis consists of three stages: data reduction, data display, conclusion drawing and verification. The result of an interview shows that there are two groups of respondents having different views, the first group looked at double duties: Taxes and Religious Contribution as subjective norm for individuals to devout Hindus and dutifully fulfilling without being influenced by tax incentives. The concept of making sincere and honest awareness shapes individual attitudes and behaviour. The second respondent group has different views, rights and obligations of the same can be done in accordance with the knowledge that it is warranted. Utilization tax on funds paid Punia Hindus are justified and act according to informants would increase the impact on the honesty of taxpayers because there is no discrimination in the tax laws.